2014
DOI: 10.1111/jofi.12150
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐Based Employee Stock Ownership: Motives and Outcomes

Abstract: Firms initiating broad-based employee share ownership plans often claim employee stock ownership plans (ESOPs) increase productivity by improving employee incentives. Do they? Small ESOPs comprising less than 5% of shares, granted by firms with moderate employee size, increase the economic pie, benefiting both employees and shareholders. The effects are weaker when there are too many employees to mitigate free-riding. Although some large ESOPs increase productivity and employee compensation, the average impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(166 citation statements)
references
References 50 publications
10
137
0
2
Order By: Relevance
“…A comprehensive study of all ESOP adoptions over 1980−2001 found that employee wages, apart from the ESOP, either increased or remained constant after adoption, so that ESOP contributions came on top of existing pay [7]. Consistent with this, comparisons of matched ESOP and non-ESOP firms found similar levels of pay and other benefits, apart from the ESOP in the two types of firms.…”
Section: Inequality and Broadly-shared Prosperitysupporting
confidence: 50%
“…A comprehensive study of all ESOP adoptions over 1980−2001 found that employee wages, apart from the ESOP, either increased or remained constant after adoption, so that ESOP contributions came on top of existing pay [7]. Consistent with this, comparisons of matched ESOP and non-ESOP firms found similar levels of pay and other benefits, apart from the ESOP in the two types of firms.…”
Section: Inequality and Broadly-shared Prosperitysupporting
confidence: 50%
“…Furthermore, increasing employee ownership diminishes the focus on growth through reduced R&D investment and commitment to innovation (Gamble, 2000) and leads to a decreased focus on maximising value and greater preference for lowering risk (Faleye et al, 2006). Recent work by Kim and Ouimet (2014) showed that increased employee ownership led to increased productivity and lowered growth.…”
Section: Employee Ownership and Performance Outcomesmentioning
confidence: 99%
“…21 ROAIA and LEVBIA are industry-adjusted return on assets and leverage ratio. We control for a battery of issuer characteristics that may correlate with PIPE and ESOP structures (Wu, 2004;Chakraborty and Gantchev, 2013;Dai, 2014;and Kim and Ouimet, 2014) defined in the Appendix. All control variables are winsorized at the 1st and 99th percentiles.…”
Section: Determinants Of White Squire Choice and Takeover Probabilitymentioning
confidence: 99%